Trends in primary percutaneous coronary intervention for the treatment of acute coronary ST-elevation myocardial infarction in Latin American countries: insights from the CECI consortium - Rodriguez-Granillo, Alfredo Matías; Solórzano, Leonardo; Pérez-Omaña, Gilberto Vladimir; Ascarrunz, Diego; Pavlovsky, Hernán; Gomez-Valerio, Reynaldo; Bertrán, Ignacio; Flores, Federico; Parra, Julio; Guiroy, Juan; Mieres, Juan; Carvajal, Francisco; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background ST-elevation myocardial infarction (STEMI) requires revascularization treatment, preferably via primary percutaneous coronary interventions (pPCI). There is a lack of data about contemporary management of STEMI in Latin America. Methods This was a multicenter, multinational, prospective, and dynamic registry of patients undergoing pPCI in Latin America for STEMI (STEMI/LATAMI Registry) that was carried out in nine centers from five countries (Argentina, Ecuador, Venezuela, Bolivia, and the Dominican Republic) between June 2021 and June 2023. All interventionalists involved in the study were originally trained at the same institution (Centro de Estudios en Cardiología Intervencionista, Buenos Aires, Argentina). The primary objective was to evaluate procedural and in-hospital outcomes of pPCI in STEMI and in-hospital outcome in the Latin America (LATAM) region; as secondary endpoints, we analyzed the following subgroups: differences between pPCI vs. pharmaco-invasive or late presenters, gender, elderly and very elderly patients, cardiogenic shock outcomes, and causes of STEMI. Results In total, 744 STEMI patients who underwent PCI between June 2021 and June 2023 in five countries (nine centers) in our continent were included; 76.3% had a pPCI, 8.1% pharmaco-invasive PCI, and 15.6% had late STEMI PCI. There were no differences in region or center when we evaluated in-hospital and 30 days of death. The rate of procedural success was 96.2%, and the overall in-hospital mortality rate was 2.2%. In the subgroup of pPCI, mean symptom onset-to-balloon time was 295.3 ± 246 min, and mean door-to-balloon time was 55.8 ± 49.9 min. The femoral approach was chosen in 60.5%. In 3.0% of patients, the left main disease was the culprit artery, with 1.63 ± 1.00 stents per patient (564 drug-eluting stents and 652 bare metal stents), with 34 patients receiving only plain optimal balloon angioplasty. Definitive stent thrombosis was related to the infarct artery as the primary cause of STEMI in 7.5% of patients. The use of assistant mechanical devices was low, at 2.1% in the pPCI group. Women were older, with large numbers in very elderly age (≥90 years), greater mortality, and incidence of spontaneous coronary dissection as a cause of STEMI (p < 0.001, p < 0.001, p < 0.001, and p < 0.003, respectively). Conclusion In suitable LATAM Centers from low/medium-income countries, this prospective registry in patients with STEMI, PCI performed by well-trained operators has comparable results to those reported in well-developed countries.